Woody Host-Specific Type III Effector HopBL2 Is Essential for Pseudomonas savastanoi Virulence and Associates With Plasmodesmata - Moreno-Pérez, Alba; Arroyo Mateo, Antonio; Rodríguez-Moreno, Luis Gabriel; Coaker, Gitta; Ramos-Rodríguez, Cayo Juan (WILEY, 2025)
The type III secretion system in Pseudomonas syringae complex pathogens delivers type III effectors (T3Es) into plant cells to manipulate host processes, enhance survival, and promote disease. While substantial research has focused on herbaceous pathogens, T3Es in strains infecting woody hosts are less understood. This study investigates the HopBL family of effectors in Pseudomonas savastanoi, a pathogen of woody plants. HopBL1 and HopBL2, core effectors in P. savastanoi, are restricted to phylogroup 3 strains of the P. syringae complex, all isolated from woody hosts. Phylogenetic analysis suggests recent horizontal acquisition of these effectors across multiple P. syringae pathovars, integrated into genomic islands flanked by mobile genetic elements. Structural analysis shows that both HopBL effectors contain SUMO protease and DNA-binding domains, with HopBL1 also possessing an ethylene-responsive motif, all characteristic of XopD from Xanthomonas spp. Despite low sequence identity, HopBL effectors exhibit structural similarity to XopD, with HopBL1 showing greater resemblance, particularly in the arrangement of these domains. Functional assays in olive and oleander revealed strain-specific contributions of HopBL1 and HopBL2 to virulence. In oleander, the natural host of P. savastanoi pv. nerii, mutation of either effector gene resulted in reduced symptom development. We show that HopBL2 localised predominantly to subnuclear foci and associated with plasmodesmata, with partial overlap observed along microtubules, suggesting a potential role in cytoskeleton manipulation. These findings underscore the importance of T3Es unique to P. syringae strains infecting woody hosts and their adaptation to modulate host cellular structures to promote disease.
Keywords: Pseudomonas; Bacterias fitopatógenas; Plantas - Enfermedades bacterianas; Plasmodesmos; Relaciones planta-patógeno; Enzimas proteolíticas; HopBL; Plasmodesmata; Pseudomonas savastanoi; Pseudomonas syringae; SUMO protease domain; Type III effector; Woody hosts